Earning While Learning: A Qualitative Study on The Practices and Challenges in Self-Regulated Learning Among Working Filipino Undergraduate Students - Aguila, Korina; Ancho, Inero; Vergara, Helga; Merca, Michelle; Gil Albor, Rufo; Pelegrina, Daisy; Almeda, Phrygian (Unib Press, 2024)
This study explores the self-regulated learning (SRL) experiences of eight working students from a state universiry in Los Banos, Laguna, Philippines. The research investigates how these students perceive and practice SRL using a phenomenological approach and semi-structured interviews. Findings reveal that working students view SRL as beneficial to their learning and employ strategies such as planning, implementing learning plans, and evaluating their performance. However, they also face individual and external challenges that hinder the effective e application of SRL. The study highlights the need for educational institutions, student support services, and policymakers to foster a positive learning environment that supports the holistic and inclusive learning needs of working students. Understanding SRL among working students is crucial in the context of the Philippine education system, particularly in a blended learning setup where students must balance academic, employment, and personal responsibilities.